PERAN MEDIA SOSIAL INSTAGRAM DALAM MEMBANGUN BRAND AWARENESS (STUDI AKUN @lavatourmerapi_Id) - Samuel Samuel; Anneke Febrina Mantiri; Wildan Rizky Rahadian; Ake Sita Fahrunisa; Bima Saputra; Fadillah Aulia Rahma; Febriella Hawa Cahyanti; Maritza Fadhila Affianti (Bogor Hospitality Journal, 2024)
In running a business, building brand awareness towards consumers is very important, because building brand awareness is one way the company can influence consumers to buy their products for the first time, and make these consumers continue to make repeat purchases. The focus of this research is on the use of Instagram social media to build brand awareness for the Lava Tour special interest tour package. This research aims to find out how to use Instagram social media in building brand awareness in local special interest tour packages in the Special Region of Yogyakarta. The approach to this research uses a qualitative descriptive approach to provide depth regarding the use of Instagram in building brand awareness. Data collection was carried out by interviewing Instagram account managers, as well as conducting observations and documentation. The results of this research explain the use of Instagram accounts, from the ten aspects studied that have fulfilled the six factors used in this research as a basis for utilizing social media to build brand awareness, although not optimally.